Enhancing EFL Learners’ Free Writing Skill with a Web 2.0 Tool ‘Storybird’; an Action Research - Çetin Köroğlu, Zeynep (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2023)
Freewriting is perceived as a pre-writing activity to collect language learners' initial ideas before the actual writing process. Unlike brainstorming activities, language learners should write their ideas and thoughts without concerning grammatical rules, spelling, punctuation or coherence, etc. throughout the given time. Freewriting activity prepares the student for an actual writing activity and enables them to produce more comprehensible and eligible texts. Current research aims to investigate whether free writing activity can be digitalized through a handy tool, which is Storybird, in preparatory classrooms. The research was carried out with 54 EFL learners in the 2019 fall term of the academic year. The participants were English language teacher candidates who have studied English for many years in Turkey. The research was designed as action research and qualitative finding were gathered. The treatment process lasted for four weeks and a written structured interview was administered at the end of the treatment process. Results of the current study show that nearly all the participants are satisfied with the utilization of Storybird in free writing activities. Additionally, they thought that the tool boosts their attitudes toward writing. The results indicate that free writing activities can be carried out digitally to make language learners more engaged and productive in writing.